Representasi Karakter Melankolis pada Peran Tanjiro dalam Film Anime Demon Slayer (Analisis Semiotika Roland Barthes) - Oktaviana Puspitasari; Iin Soraya; Sari Ekowati Hadi (Tamilis Synex: Multidimensional Collaboration, 2025)
The problem that will be discussed in this research is "How is the representation of Kamado Tanjiro's melancholic character from the depiction of signs in the film Demon Slayer: Kimetsu no Yaiba - To The Hashira Training Training, the aim of this research is to find out how Kamado Tanjiro's melancholic personality is represented in the anime film Demon Slayer: Kimetsu no Yaiba – To The Hashira Training Training. The method used in this research is qualitative analysis, namely by collecting data in the form of words (spoken and written) and verbally. The aim is to identify the melancholic character of the characters in anime films. In this research, ten scenes were found that depict melancholic characters, which were observed through observation based on melancholic character traits determined by experts, where Kamado Tanjiro is a warm person, cares about other people, really loves his family, friends and other people. the people around him, as well as trying hard, remain focused on the goal of saving the village of sword people from demon attacks, so he must be willing to sacrifice his sister, Nezuko, in order to achieve victory even though his heart continues to churn with guilt. So it can be concluded that, Kamado Tanjiro in this film is depicted as a melancholic figure who has the characteristics of often reminding himself of painful events, easily feeling guilty, low self-esteem, focused on goals, often lost in his own thoughts, having difficulty in making decisions, calm. , have sensitive feelings and can make sacrifices for the sake of others.